2012
DOI: 10.12659/msm.882887
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic fatigue resistance of Mtwo NiTi rotary instruments used by experienced and novice operators – an in vivo and in vitro study

Abstract: SummaryBackgroundThe aim of the present study was to evaluate the cyclic fatigue resistance of Mtwo NiTi rotary instruments after clinical use by 1 experienced and 1 novice operator.Material/MethodsCyclic fatigue testing of instruments was performed on tapered artificial canals with a 5 mm radius of curvature and 60° angle of curvature. Twenty Mtwo instruments for each size were selected and divided into 2 groups: group A consisted of 10 instruments of each size used for shaping 10 root canals in molar teeth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…When the endodontic literature is reviewed, it is shown that there are many factors that affect the CFR of NiTi rotary files. These factors include angle and radius of the canal curvature, instrument size and taper, movement kinematics, speed of rotation, effect of sterilisation, as well as many other variables such as operator's skill and experience, which may help to explain the variations in the prevalence of CFR among different studies . Recently, some studies focused on whether or not temperature affects the CFR of NiTi rotary files in addition to the factors mentioned above .…”
Section: Introductionmentioning
confidence: 99%
“…When the endodontic literature is reviewed, it is shown that there are many factors that affect the CFR of NiTi rotary files. These factors include angle and radius of the canal curvature, instrument size and taper, movement kinematics, speed of rotation, effect of sterilisation, as well as many other variables such as operator's skill and experience, which may help to explain the variations in the prevalence of CFR among different studies . Recently, some studies focused on whether or not temperature affects the CFR of NiTi rotary files in addition to the factors mentioned above .…”
Section: Introductionmentioning
confidence: 99%